1997
DOI: 10.1104/pp.114.4.1247
|View full text |Cite
|
Sign up to set email alerts
|

The Ascorbate Carrier of Higher Plant Plasma Membranes Preferentially Translocates the Fully Oxidized (Dehydroascorbate) Molecule

Abstract: Recently, the uptake of 14C-labeled ascorbate (ASC) into highly purified bean (Phaseolus vulgaris 1.) plasma membrane vesicles was demonstrated in our laboratory. However, the question of the redox status of the transported molecule (ASC or dehydroascorbate [DHA]) remained unanswered. I n this paper we present evidence that DHA i s transported through the plasma membrane. High-performance liquid chromatography analysis of the redox status of ASC demonstrated that freshly purified plasma membranes exhibit a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 28 publications
7
38
0
Order By: Relevance
“…In salt-treated pea plants, uptake of the oxidized ASC through the plasma membrane may represent an important step in the regeneration of apoplastic ASC. Such ASC regeneration has been described by Horemans et al (1996Horemans et al ( , 1997, who demonstrated the existence of a carrier-mediated ASC/DHA transport system that preferentially translocates DHA from the apoplast to the cytosol and that probably exists to reduce this molecule in this cell compartment (Castillo and Greppin, 1988;Luwe et al, 1993;Horemans et al, 1997). This mechanism could be occurring in both pea cultivars, although its efficacy seems to be rather low in NaCl-stressed plants, particularly in pea cv Lincoln.…”
Section: Discussionmentioning
confidence: 77%
“…In salt-treated pea plants, uptake of the oxidized ASC through the plasma membrane may represent an important step in the regeneration of apoplastic ASC. Such ASC regeneration has been described by Horemans et al (1996Horemans et al ( , 1997, who demonstrated the existence of a carrier-mediated ASC/DHA transport system that preferentially translocates DHA from the apoplast to the cytosol and that probably exists to reduce this molecule in this cell compartment (Castillo and Greppin, 1988;Luwe et al, 1993;Horemans et al, 1997). This mechanism could be occurring in both pea cultivars, although its efficacy seems to be rather low in NaCl-stressed plants, particularly in pea cv Lincoln.…”
Section: Discussionmentioning
confidence: 77%
“…Inhibition studies showed that Asc uptake into H. vutgare protoplast was sensitive towards sulfhydryl reagents, N-ethyl maleimide (NEM), p-chloromercuribenzenesulfonic acid (pCMBS), and ionophores (gramicidin and valinomycin). Similar experiments on Asc uptake in purified membrane vesicles from P. vulgaris did not result in any significant inhibition of the transport activity (Horemans et al 1996). The observed differences could possibly indicate that different Asc uptake mechanisms operate in plants depending on the tissue or species studied.…”
Section: Introductionmentioning
confidence: 80%
“…Rautenkranz et al (1994) and Foyer and Lelandais (1996) demonstrated uptake of vitamin C into protoplasts isolated respectively from Hordeum vulgare and Pisum sativum leaves, These in vivo experiments strongly suggested the presence of an Asc transport mechanism in the plant plasma membrane. In recent work we were able to identify the activity of an Asc carrier in highly purified plasma membrane vesicles of Phaseolus vulgaris (Horemans et al 1996(Horemans et al , 1997. Recent results on the activity of the Asc carrier in purified plasma membrane vesicles of P. vulgaris suggested that this system operates via a counterflow mechanism whereby uptake of a DHA molecule is accompanied by the export of an Asc molecule (Horemans et al 1998).…”
Section: Introductionmentioning
confidence: 95%
“…These include: a) the rate of ascorbate transport into the apoplastic fluid; b) the amount of 03 reaching apoplastic fluid via the stomata (e.g., stomata, like animal airways, have variable resistances, and if this resistance is increased, less 03 can be expected to penetrate into the apoplastic space); c) other reactions of ascorbate within the apoplastic fluid (e.g., utilization by the ascorbate peroxidase system and possible recycling of vitamin E in underlying plasma membranes); and d) possible regeneration of oxidized ascorbate by plasma membrane reductive mechanisms (64). With regard to the latter, it should be recognized that although ascorbate transport system(s) across the plamalemma of animal cells is a well-documented phenomenon (65,66), ascorbate transport system(s) across the plant plasmalemma are only beginning to be described (67,68) and, in fact, knowledge about the precise pathways and metabolic controls of ascorbate biosynthetic pathways is still incomplete (52). Importantly, dehydroascorbate (and perhaps more importantly monodehydroascorbate) reductase systems are more active in plant cells than in animal cells, although the specific reductase systems are multiple and vary in their adaptive responses to oxidative stress (69,70).…”
Section: Structural Considerationsmentioning
confidence: 99%